A framework for developing and using a predictive delivery performance measurement system. (14th March 2006) - Unahabhokha, Chatchai; Platts, Ken; Tan, Kim Hua
Traditional performance measurement systems encourage companies to measure historical delivery performance and respond to what has already happened. This paper presents a framework for developing a predictive delivery performance measurement system for organisations. The framework consists of three main sections. The first presents a methodology and criteria for selecting key predictors for a delivery performance of a particular production order. The second section presents a tool used to develop a predictive mechanism which helps to predict a delivery performance from the selected key predictors. The third section shows how a preventive system could work to help manage an unfavourable predicted delivery performance outcome. This paper first describes the methodology used to develop the framework and then the framework in detail. Then a case study is used to illustrate the application of the framework. Finally, results and discussion from the case study are reported and potential future research is discussed.